Designing a wireless network - Wheat, Jeffery A.; Syngress Media, Inc. (Rockland, Mass. : Syngress Pub., 2002)
Business is on the move - mobile computing must keep up! Innovative technology is making the communication between computers a cordless affair. Mobile computing with laptops, hand helds and mobile phones is increasing the demand for reliable and secure wireless networks. Network engineers and consultants need to create and build cutting-edge wireless networks in both the small business and multi-million dollar corporations. Designing Wireless Networks provides the necessary information on how to design and implement a wireless network. Beginning with detailed descriptions of the various implementations and architectures of wireless technologies and moving to the step-by-step instructions on how to install and deploy a fixed wireless network; this book will teach users with no previous wireless networking experience how to design and build their own wireless network based on the best practices of the Enhanced Services from Lucent Technologies. * Timely coverage of new technologies: Communication without cables is the future of netwoking * Advocates wireless networking solutions for any user, regardless of location, device or connection. * Written by Experts. The authors are leading WAN authorities at Lucent Technologies. * No previous wireless experience is assumed, however, readers should have a basic understanding of networking and TCP/IP protocols.
Includes index.
Step-by-step instructions for designing a wireless project from inception to completion ... everything you need to know about Bluetooth, LMDS,802.11, and ... complete coverage of fixed wireless, mobile wireless, and optical wireless technology ... cover.
Keywords: Wireless communication systems; Electronic books